Pengaruh Hutang Modal Dan Aset Terhadap Profitabilitas Perusahaan Di Bursa Efek Indonesia - Akhmad Syarifudin (Politeknik Dharma Patria Kebumen, 2021)
This study examines the effect of debt and asset growth on profitability (ROE). The population of the company is LQ45 on the IDX. The sample criteria were divided into 2, namely group I DAR <50% and II DAR> 50%. The goal is to determine the profitability between groups. Multiple linear regression data analysis techniques. The test results in group I DAR and DER have no significant effect. Asset growth has a significant effect, while LDER has a negative effect on ROE. The results in group II DAR, DER, and Asset Growth do not have a significant effect, while LDER has a negative effect on ROE. Simultaneously the variables in group I have a positive effect on ROE, while in group II the simultaneous test has a significant effect if the confidence level is lowered at 90%. The profitability of group I averaged 17.04% below the ROE of Group II which averaged 23.89%. The essence is that changes in debt are not effective at boosting profitability, an increase in debt risks reducing profits. The implication is that companies must explore sources of capital other than debt in order to increase profitability. This fundamental analysis provides information for investors as well as demonstrates the importance of paying attention to other factors as a consideration for business decisions.